Risks of respiratory effects among residents living nearby rice mill in tumpat, Kelantan - Zailani, Nur Salshabila Afifah (Universiti Sains Malaysia, 2016)
Many studies that have been conducted shows that industrial air pollution can trigger significant respiratory health effects on population that lived in the nearby area. This cross sectional study was carried out to investigate the lung function and respiratory symptoms of residents living near to a rice mill in Tumpat, Kelantan. This study also aimed to determine the average and differences of PMio concentration at residential areas located at 1 and 2 km radius from the factory. The study population consisted of 47 residents who lived near to the factory. They were interviewed using respiratory questionnaires and lung function test also was performed. PMio measurements were carried out for 8 hours at 8 sampling points around the residential area. Morning cough and phlegm were the most common symptoms experienced by the residents. Duration of residence was significantly associated with breathlessness (p = 0.004) and morning phlegm (p = 0.026). Age of residents was significantly associated with both morning cough (p = 0.028) and morning phlegm (p = 0.032). Smoking status was found associated with morning cough (p = 0.008), morning phlegm (p = 0.002) and chest illness (p = 0.022). Lung condition were found to have significant association with morning cough (p = 0.020) and morning phlegm (p = 0.048). Overall, lung function capabilities of the residents were reduced. Lung function capabilities of males were higher than female residents. There was significant difference of FEV] between male and female residents. Most of residents have restrictive lung impairments. There was significant difference in PMio concentration between residential areas located at 1 km and 2 km radius (p < 0.001). In conclusion, residents living nearby rice mill have high risk of respiratory problems. This can be worsen by various risk factors including gender, age, duration of residence and smoking status.